DOI: 10.3990/1.9789036529358
|View full text |Cite
|
Sign up to set email alerts
|

Electronic devices fabricated at CMOS backend-compatible temperatures

Abstract: Cover: illustration of the main process steps described in the dissertation: green-laser crystallization of preformed a-Si film and deposition of functional multilayer stack (SiO 2 , Si-nanodots, Al 2 O 3 , Al-metallization).Cover design: Oleg Vorobyov

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 135 publications
(202 reference statements)
0
6
0
Order By: Relevance
“…Van der Pauw [68] showed that, if (i) the contacts are sufficiently small (point-like), (ii) the sample material is homogeneous in thickness, (iii) the contacts are at the circumference of the sample and (iv) the surface is singly connected (does not contain isolated holes), then R 12,34 and R 41,23 are related by 12,34 41,23 exp(…”
Section: Four-point Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Van der Pauw [68] showed that, if (i) the contacts are sufficiently small (point-like), (ii) the sample material is homogeneous in thickness, (iii) the contacts are at the circumference of the sample and (iv) the surface is singly connected (does not contain isolated holes), then R 12,34 and R 41,23 are related by 12,34 41,23 exp(…”
Section: Four-point Methodsmentioning
confidence: 99%
“…where F is a function only of the ratio R r = R 12,34 /R 41,23 , satisfying the relation 4.532 ln (2) tR tR…”
Section: Four-point Methodsmentioning
confidence: 99%
See 3 more Smart Citations